The Contribution of Efflux Pumps in Mycobacterium abscessus Complex Resistance to Clarithromycin - Júlia S. Vianna; Diana Machado; Ivy B. Ramis; Fábia P. Silva; Dienefer V. Bierhals; Michael Andrés Abril; Andrea von Groll; Daniela F. Ramos; Maria Cristina S. Lourenço; Miguel Viveiros; Pedro E. Almeida da Silva (MDPI AG, 2019)
The basis of drug resistance in Mycobacterium abscessus is still poorly understood. Nevertheless, as seen in other microorganisms, the efflux of antimicrobials may also play a role in M. abscessus drug resistance. Here, we investigated the role of efflux pumps in clarithromycin resistance using nine clinical isolates of M. abscessus complex belonging to the T28 erm(41) sequevar responsible for the inducible resistance to clarithromycin. The strains were characterized by drug susceptibility testing in the presence/absence of the efflux inhibitor verapamil and by genetic analysis of drug-resistance-associated genes. Efflux activity was quantified by real-time fluorometry. Efflux pump gene expression was studied by RT-qPCR upon exposure to clarithromycin. Verapamil increased the susceptibility to clarithromycin from 4- to ≥64-fold. The efflux pump genes MAB_3142 and MAB_1409 were found consistently overexpressed. The results obtained demonstrate that the T28 erm(41) polymorphism is not the sole cause of the inducible clarithromycin resistance in M. abscessus subsp. abscessus or bolletii with efflux activity providing a strong contribution to clarithromycin resistance. These data highlight the need for further studies on M. abscessus efflux response to antimicrobial stress in order to implement more effective therapeutic regimens and guidance in the development of new drugs against these bacteria.